Hemostasis radiotherapy for gastric cancer: Usefulness of the gastric cancer to spleen apparent diffusion coefficient ratio - Osamu Tanaka, MD (Elsevier, 2022)
The hemostatic effect of radiation therapy on gastric cancer with bleeding is known. However, blood tests and endoscopes are mainly used to determine the therapeutic effect. Additionally, magnetic resonance imaging has been reported to be useful when needed because endoscopes are invasive. In this study, magnetic resonance diffusion-weighted imaging was used to evaluate the hemostatic effect of gastric cancer. The hemostatic effect and apparent diffusion coefficient value were correlated. The apparent diffusion coefficient value was also effective in salvage irradiation during rebleeding. Although the apparent diffusion coefficient value of gastric cancer did not change during rescue irradiation, the degree of hemostatic effect could be evaluated in more detail by using the ratio of the apparent diffusion coefficient values of diffusion-weighted imaging of gastric cancer and the spleen. In the future, it would be desirable to use diffusion-weighted imaging instead of endoscopy to evaluate the gastric cancer to spleen apparent diffusion coefficient ratio in a large number of cases.